2018
DOI: 10.1155/2018/8058291
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HIV Status Disclosure and Its Effect on Treatment Adherence and Quality of Life among Children 6–17 Years on Antiretroviral Therapy in Southern Highlands Zone, Tanzania: Unmatched Case Control Study

Abstract: Background The World Health Organization (WHO) recommends that children should be informed of their HIV status at ages 6 to 12 years and full disclosure of HIV and AIDS be offered in a caring and supportive manner at about 8 to 10 years. The objective of this study was to determine factors associated with HIV status disclosure and its effect on treatment adherence and health-related quality of life among children between 6 and 17 years of age living with HIV/AIDS in the Southern Highlands Zone, Tanzania, 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
(25 reference statements)
1
27
1
1
Order By: Relevance
“…Findings showed that the rate of full disclosure of status to children living with HIV is still low in Ghana. Although this rate of disclosure is considered to be low, it is slightly higher compared to those reported in Kenya [ 31 ], the Dominican Republic [ 29 ], Zimbabwe [ 32 ], and earlier figures reported in Ghana [ 15 ]. The low rate of disclosure of HIV status could be attributed to the fact that the majority of the children who participated in this study were younger, and it has been established that older children and adolescents are more likely to have their HIV status disclosed to them than younger children [ 15 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 57%
“…Findings showed that the rate of full disclosure of status to children living with HIV is still low in Ghana. Although this rate of disclosure is considered to be low, it is slightly higher compared to those reported in Kenya [ 31 ], the Dominican Republic [ 29 ], Zimbabwe [ 32 ], and earlier figures reported in Ghana [ 15 ]. The low rate of disclosure of HIV status could be attributed to the fact that the majority of the children who participated in this study were younger, and it has been established that older children and adolescents are more likely to have their HIV status disclosed to them than younger children [ 15 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 57%
“…This study is supported by studies conducted in Bale, Gondar, Nigeria, South Africa, Tanzania, and Zimbabwe. 13 , 14 , 21–23 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…In SSA, HRQoL studies have mostly been conducted among clients who access ART in clinical settings [24,[26][27][28]. Differentiated service delivery (DSD) is a patientcentered approach which offer virally suppressed PLHIV alternative models of HIV care both within clinic (e.g.…”
Section: Introductionmentioning
confidence: 99%